Jungle journey a push and pull adventure - Black, Allison (London ladybird books, 2019)
Curious minds will love to explore the dark recesses of the jungle with this interactive title from Little World. Discover all sorts of creatures high up in the canopy and on the jungle floor in this bright and colourful board book, which features a novelty to slide, push or pull on every spread
English stories
Keywords: Jungle animals Juvenile fiction; Toy and movable books; English stories